Selected documents of the international petroleum industry - Organization of Petroleum Exporting Countries (Vienna : Organization of the Petroleum Exporting Countries, 1968)
The book examines issues of petroleum with particular reference to member and other countries legislation as well as new oil agreements among others.
usc 22/01/2019
Loans
Keywords: Petroleum law and legislation; Petroleum law and legislation